1993
DOI: 10.1038/hdy.1993.89
|View full text |Cite
|
Sign up to set email alerts
|

Selection against inbreds in early life-cycle phases in Pinus leucodermis Ant.

Abstract: Conifers are self-compatible hermaphroditic plants which usually show very low levels of selfing and severe inbreeding depression. Positive fixation indices are observed in the seed stage owing to partial selfing but not in the adult stage and selection against inbreds has been frequently invoked to explain this observation. To determine the stage of elimination of inbreds in Pinus leucoderinis Ant., a narrow-ranged and relic species characterized by 18-28 per cent selling rates, fixation indices at isozyme ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 14 publications
0
21
0
3
Order By: Relevance
“…There seems to be no strong selection against inbred progeny because the adult sample also had an excess of homozygotes. In other studies, a decrease of F-values has been reported with increasing age of the analysed ontogenetic stages (Morgante et al, 1993). Another factor that might have contributed to the high values of F in Paracou is the Wahlund effect.…”
Section: Heterozygositymentioning
confidence: 96%
“…There seems to be no strong selection against inbred progeny because the adult sample also had an excess of homozygotes. In other studies, a decrease of F-values has been reported with increasing age of the analysed ontogenetic stages (Morgante et al, 1993). Another factor that might have contributed to the high values of F in Paracou is the Wahlund effect.…”
Section: Heterozygositymentioning
confidence: 96%
“…I), though only for the three trinucleotide loci this determined a significant departure from Hardy-Weinberg equilibrium, either within population or in the global sample. Homozygote excess has been so far shown in conifers mostly in juveniles [17], and it is possible that the type of tissue we have used for this study (seedlings or pools of megagametophytes) shows the same type of departure from equilibrium. However, only EATC1G02 showed distortion at the population level in 3 populations out of 4.…”
Section: Diversity Parameters and Global F St Values Are Shown Inmentioning
confidence: 99%
“…However, two sources of bias could affect our estimation: (a) in spite of high exclusion probabilities, exclusion analysis has low power when the number of potential parents in the population is high [12]; and (b) selfs generated by parent trees outside the plot were not considered. In Pinus species, selection against inbreeds is expected to be extensive at the seed stage ( [24] and references within) whereas it has only been shown in some species to occur shortly after germination (Pinus leucodermis [33], Pinus sylvestris [34]). In maritime pine, most lethal or sublethal alleles are probably eliminated during seed formation and germination as well as during the first growing season.…”
Section: Discussionmentioning
confidence: 99%